TRANSFORMATION OF ADMINISTRATIVE MANAGEMENT BASED ON DIGITAL TECHNOLOGY IN IMPROVING THE EFFECTIVENESS OF ISLAMIC EDUCATIONAL SERVICES - Haeroni Haeroni; Abdullah Abdullah (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
This research aims to understand how the process of management transformation in the digital-based administration at MA Nurul Jadid works. This transformation is an effort to enhance the effectiveness and efficiency of school administrative services through the utilization of digital technology. The process of transformation in the management of MA Nurul Jadid is carried out through three main stages: planning, implementation, and evaluation. The planning stage includes resource preparation, strategy development, and goal setting; the implementation stage focuses on the application of digital systems in administrative activities; while the evaluation stage is conducted to assess the program's success and identify the challenges faced for future improvements. The approach used in this research is case study, which is part of qualitative research methods. This approach aims to explore a specific case in depth by collecting information from various sources, resulting in descriptive data in the form of written or spoken words from people as well as observed behaviors